Isoprenylated phenolic compounds with tyrosinase inhibition from Morus nigra. Issue 5 (4th May 2018) - Hu, Xiao; Yu, Mei-Hua; Yan, Gui-Rui; Wang, He-Yao; Hou, Ai-Jun; Lei, Chun
Abstract: A new isoprenylated sanggenon-type flavanone, nigrasin K (1 ), together with three known analogs (2 –4 ) and five known Diels–Alder adducts (5 –9 ), were isolated from the twigs of Morus nigra . Their structures were elucidated by spectroscopic methods. Sanggenon M (2 ), chalcomoracin (5 ), sorocein H (6 ), kuwanon J (7 ), sanggenon C (8 ), and sanggenon O (9 ) showed significant inhibitory effects on mushroom tyrosinase. Abstract :